Pengaruh Model Pembelajaran Inkuiri Terbimbing Menggunakan Alat Laboratorium Terhadap Hasil Belajar Peserta Didik - Silviana, Baiq Dara; Ayub, Syahrial; Wahyudi, Wahyudi (Universitas Hamzanwadi, 2023)
The purpose of this research is to find out whether there is an influence of the guided inquiry learning model using laboratory tools on student learning outcomes. This type of research uses an experimental type with a pretest-posttest control group design. The sampling technique used the Cluster Random Sampling method and obtained class XI MIPA 2 with 29 students as the experimental class, and class XI MIPA 3 with 27 students as the control class. The experimental class was given a learning treatment using a guided inquiry model using laboratory equipment, while the control class used conventional learning. The instrument used to measure student learning outcomes is an objective test in the form of multiple choice of 25 questions. The learning outcomes test instrument used has been tested for validity, reliability test, level of difficulty test, and differential power test. The data analysis technique was carried out by polled variance t-test. The results of the t-test pre-test and post-test values are (t-count) greater than (t-tables) at a significant level of 5% categorized ( ) rejected and ( ) accepted. So it can be concluded that there is an influence of the guided inquiry learning model using laboratory tools on student learning outcomes.